CRITICISMS ON ONTOLOGICAL RELATIVISM OF MODERN SCIENCE BY SYED MUHAMMAD NAQUIB AL-ATTAS AND SEYYED HOSSEIN NASR - Khalina Mohammed Khalili, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2024)
Postmodern approaches to science introduce various methods, and result in multiple explanations and competing theories. This has exacerbated the science war in philosophy of science. The ongoing disputes known as ‘science war’ is a consequence of ontological disputes within the philosophical branch of metaphysics. Even though science had denied the importance of metaphysics in its practice, this paper argues that the recognition of philosophy specifically that in regards to metaphysics is a solution to the confusion arising from relativism of knowledge. As part of a preliminary attempt to confront this problem, this paper focuses on the criticisms of Syed Muhammad Naquib al-Attas and Seyyed Hossein Nasr on the ontology of modern science, which issues from the denial of metaphysics by modern scientists. Their views on ontology are part of both scholars’ Islamic philosophy of science. This is a qualitative research based on historical, doctrinal and comparative analysis of the primary works by the two scholars. The arguments are presented within the scope of philosophy of science based on the framework of the Islamic intellectual tradition. Thus, we find that a wider and transcendental epistemology is possible for understanding the multiple levels of reality subsumed within the metaphysics of Islam, which opens the door to reality and truth.